2003
DOI: 10.4049/jimmunol.170.7.3662
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Receptor Agonism Impairs the Efficiency of the Local Immune Response by Altering Trafficking of Naive and Antigen-Activated CD4+ T Cells

Abstract: FTY720 (2-amino-[2-(4-octylphenyl) ethyl]-1,3-propanediol hydrochloride) is an immunosuppressive agent that inhibits allograft rejection. We recently demonstrated that FTY-phosphate, the active metabolite of FTY720, acts as a full agonist for sphingosine-1-phosphate (S1P) receptors. Furthermore, activation of S1P receptors with their natural ligand, S1P, as well as pharmacological ligands leads to lymphopenia, probably due to sequestration of lymphocytes in secondary lymphoid organs. In the present study we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 22 publications
4
93
1
Order By: Relevance
“…In conventional T cells, S1P also regulates migration from the thymus and secondary lymphoid organs into the circulatory system, and cytokine production by the downregulation of IL-4 and Role of FTY720 in cytokine production of NKT cells SJ Hwang et al IFN-g and enhancement of IL-10 production as shown in Figure 3a, 21 whereas FTY720 does not alter cytokine production in T cells. 18,25 Unlike NKT cells, two types of S1P receptors are differentially responsible for the regulation of migration and cytokine production in T cells: S1P 1 enhances the migration of T cells, whereas S1P 4 modulates cytokine production by T cells. 21 In addition, S1P 5 regulates NK cell trafficking in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conventional T cells, S1P also regulates migration from the thymus and secondary lymphoid organs into the circulatory system, and cytokine production by the downregulation of IL-4 and Role of FTY720 in cytokine production of NKT cells SJ Hwang et al IFN-g and enhancement of IL-10 production as shown in Figure 3a, 21 whereas FTY720 does not alter cytokine production in T cells. 18,25 Unlike NKT cells, two types of S1P receptors are differentially responsible for the regulation of migration and cytokine production in T cells: S1P 1 enhances the migration of T cells, whereas S1P 4 modulates cytokine production by T cells. 21 In addition, S1P 5 regulates NK cell trafficking in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, FTY720 does not impair T-cell functions, such as activation or cytokine production. 18,25 A recent study has shown that S1P 1,2 and S1P 4 mRNA were significantly detected in invariant NKT cells, whereas the transcription level of S1P 3 was relatively low, 26 suggesting that NKT cells express various S1P receptors. Moreover, it was reported that the S1P1 receptor (S1P 1 ) is essential for the migration of NKT cells from the thymus into the peripheral lymphoid tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of donor Bcl-2 clone 4 T cells to infiltrate the pancreatic islets led us to question whether the accumulation of Bcl-2 clone 4 T cells was due to increased islet damage and thus, the increased availability of Ag, or other factors such as the inhibition of apoptosis or increased cytokine production. To prevent the initiation of Bcl-2 clone 4 T cell-mediated islet damage, InsHA recipient mice were first treated with an S1P receptor-1 agonist drug (FTY720) that has been shown to prevent lymphocyte egress from the LNs (33,34,36). Treatment with FTY720 had no effect on the activation, proliferation, or accumulation of Bcl-2 clone 4 T cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The sphingosine-1-phosphate receptor-1 agonist (FTY720) was generously provided by Dr. Hugh Rosen (The Scripps Research Institute) (33)(34)(35)(36) To measure CD8 T cell apoptosis in vivo, single-cell suspensions were prepared from the peripheral and pancreatic LN and Annexin V staining was measured by flow cytometry using Annexin V-allophycocyanin staining Ab (BD Biosciences) according to the manufacturer's instructions. Briefly, cells were stained with Pacific Blue-conjugated anti-CD8 mAb (Caltag Laboratories) and PE-conjugated anti-Thy1.1 mAb (BD Pharmingen) followed by washing twice with cold PBS and then re-suspended in 1ϫ binding buffer at a concentration of 1 ϫ 10 6 cells/tube.…”
Section: Fty720 Treatmentmentioning
confidence: 99%